From Sham to Reality: Should a Wrong Be Taxed as a Right? - Sprysak, Chris (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
How should a sham be treated for tax purposes? In 1524994 Ontario Ltd. v. M.N.R., the Federal Court of Appeal treated a sham as if it reflected the true agreement between the parties in order to uphold a GST assessment. The result was inconsistent with existing jurisprudence and undesirable. Courts should apply the law to the true facts only, and should not overlook or give effect to a sham in order to achieve the desired juridical consequences.The author reviews the origins and development of the sham doctrine and introduces a three-part typology of sham cases. In situations like 1524994 Ontario Ltd. v. M.N.R., the sham is intended to obtain non-tax benefits from a third-party victim, but in the process triggers unintended tax consequences, which are the subject of litigation. Although the traditional approach in Continental Bank Leasing Corp. v. M.N.R. (under which recharacterization is permissible only if the label attached to a transaction does not reflect its actual legal effect) could result in non-payment of taxes and retention of improperly obtained benefits, the author concludes that this result would be preferable to that of the Federal Court of Appeal judgment. Treating a sham as real, and taxing a wrong as a right (1) will not deter parties from creating shams to obtain non-tax benefits, (2) will violate longstanding principles that tax law be applied with neutrality and equity and without considering its effects, and (3) will increase uncertainty and inconsistency in the case law.